"They Don't Trust Us": The Influence of Perceptions of Inadequate Nursing Home Care on Emergency Department Transfers and the Potential Role for Telehealth. (March 2020) - Stephens, Caroline E.; Halifax, Elizabeth; David, Daniel; Bui, Nhat; Lee, Sei J.; Shim, Janet; Ritchie, Christine S.
In this descriptive, qualitative study, we conducted eight focus groups with diverse informal and formal caregivers to explore their experiences/challenges with nursing home (NH) to emergency department (ED) transfers and whether telehealth might be able to mitigate some of those concerns. Interviews were transcribed and analyzed using a grounded theory approach. Transfers were commonly viewed as being influenced by a perceived lack of trust in NH care/capabilities and driven by four main factors: questioning the quality of NH nurses' assessments, perceptions that physicians were absent from the NH, misunderstandings of the capabilities of NHs and EDs, and perceptions that responses to medical needs were inadequate. Participants believed technology could provide "the power of the visual" permitting virtual assessment for the off-site physician, validation of nursing assessment, "real time" assurance to residents and families, better goals of care discussions with multiple parties in different locations, and family ability to say goodbye.